Rancang Bangun Sistem Oil Change Reminder Sepeda Motor Berbasis Mikrokontroler Menggunakan Android - Rakan El Fawwaz; Dodon Yendri (Universitas Andalas, 2020)
This study aims to create a tool that can monitor motorcycle distance through a mobile application and provide an oil change reminder based on distance to the user through the telegram application. This system consists of three main components, namely embedded systems, mobile applications, and Realtime Databases. The embedded system consists of a Wemos D1 microcontroller and Hall effect Sensor. based on tests conducted the system can read motorcycle distances and save distance data into a Realtime Database and provide reminders to users, this system relies on an internet network, where the error rate of this system that is tested on unstable internet locations has the highest error rate of 79, 9% and lowest 59.3%, then the second condition was tested in locations with stable internet networks that had the highest error rate of 1% and the lowest 0%.